Frontal Cortex-Like Functions of the Subthalamic Nucleus - Baunez, Christelle; Lardeux, Sylvie (Frontiers in Systems Neuroscience, 2011)
The subthalamic nucleus has been considered a motor structure for a long time. Over the last twenty years, anatomical and behavioral data have highlighted the position of the STN within a prefrontal-associative and a limbic loop, suggesting that the STN should play a critical role in frontal functions such as attention, inhibitory control (including impulsive action, compulsivity, impulsive choice) and motivation. Here we will review the work highlighting these functions of STN.